Desenvolvimento de aplicativo móvel para orientação especializada em rotinas de exercícios físicos - ARRAES, Ricardo Bastos (2020)
The consolidation of mobile devices is one of the greatest technological revolutions of mankind that has been reshaping the interaction between people. These devices have a great potential to improve the interaction between Physical Education teachers and their students, overlapping other similar solutions that, in fact, ignore the importance of this relationship. This work presents a project aimed at the development of an application that allows the teacher to participate actively in the routine of his student’s training through the management of training records and physical assessments; And the student, to follow their results in a more practical way.